Towards a sustainable approach to clustering small-scale farmers to market their agricultural produce - Murray-Prior, Roy; Batt, Peter; Concepcion, S.; Montiflor, M.; Axalan, J.; Lamban, Ruby J.G.; Real, Rodel R.; Israel, Floro; Bacus, Ricarte G.; Apara, Dante I. (Society for Global Business & Economic Development (SGBED), 2011)
The University of the Philippines Mindanao and Curtin University have been organising small-scale vegetable farmers in Mindanao into cluster marketing groups to improve their access to markets and returns from the sale of their vegetable products using the 8-Step Clustering Approach for Agroenterprise Development developed by the Catholic Relief Services (Philippines). This paper reports on an action research investigation with around 30 marketing clusters. Cluster marketing has led to: better and wider market access, improved prices, reduced costs, improved human capital and social capital, and higher incomes. However, the current process may not lead to sustainable cluster marketing without support and may lead to dependency. This paper discusses strategies to overcome key challenges identified and deficiencies in the current process and suggests changes to the 8-step process so that it may improve the chances of cluster success and sustainability.